2016
DOI: 10.17261/pressacademia.2016116541
|View full text |Cite
|
Sign up to set email alerts
|

The association between perceived job insecurity and career commitment in hospitality sector: the role of support at work

Abstract: ABSTRACThe purpose of this study is to investigate the relationship between perceived job insecurity, career commitment. The study also attempts to examine the mediating effect of support at work on this relationship. A survey from 186 hospitality employees was analyzed using mediated regression analysis. The results demonstrate that perceived job insecurity is negatively related to career commitment. High supervisor and peer support contributes to career commitment and mediates the association between the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Adopting it in any hospitality organization reduces workers’ intentions to quit. Other related concepts involve support from top management and co-workers [ 13 , 19 , 20 ]. Researchers have indicated that it is unlikely for workers to experience JI and develop turnover intentions when they receive enough support from fellow employees and organizational leadership.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Adopting it in any hospitality organization reduces workers’ intentions to quit. Other related concepts involve support from top management and co-workers [ 13 , 19 , 20 ]. Researchers have indicated that it is unlikely for workers to experience JI and develop turnover intentions when they receive enough support from fellow employees and organizational leadership.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In another empirical piece, Kong et al (2012) demonstrated that career commitment enhanced hotel managers’ career competencies. A study of hotel employees documented that job insecurity mitigated career commitment (Akbiyik, 2016). The findings of a study associated with the foodservice industry showed that intrinsic orientation and obligatory norms positively affected career commitment directly and indirectly through WE (Lin et al , 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Bu durum istihdam algısının azalmasıyla birlikte işten ayrılma niyetinin artmasından dolayı kaynaklanabilmektedir (Bozkurt ve Özkoç, 2018). Akbıyık (2016) sağlık çalışanları üzerine gerçekleştirdiği bir çalışmada iş güvencesizliği algılayan çalışanların kariyer bağlılıklarının azaldığını gözlemlemiştir. Benzer şekilde Laine, Heijden, Wickstrom, Hasselhorn ve Tackenberg (2009) hemşirelerin iş güvencesizliği algılarının artmasıyla birlikte mesleklerini bırakma niyetlerinin de arttığı sonucunu ortaya koymuşlardır.…”
Section: Değişkenler Arasındaki İlişkilerunclassified